Effects of the irrigation and of the integration between setaria-grass and ryegrass pastures on milk production - Alvim, Maurilio José; Martins, Carlos Eugênio; Brotel, Milton de Andrade; Salvati, José Augusto; Jacob, Maria Auxiliadora Miguel (Pesquisa Agropecuaria Brasileira, 1993)
The experiment was carried out at the Embrapa-Centro Nacional de Pesquisa de Gado de Leite, in Coronel Pacheco, MG, Brazil, during two periods of dry season. The objective was to evaluate the milk production from crossbred Holstein-Zebu cows kept exclusively under setaria-grass (Setaria sphacelata (Schum.) Moss., cv. Kazungula) and ryegrass (Lolium multiflorum Lam.) grazing conditions. Treatments were: (T1) = cows grazing on irrigated setaria, plus two to three hours grazing ryegrass; (T2) = cows grazing on setaria without irrigation, plus two to three hours grazing ryegrass; and (T3) = cows grazing on irrigated setaria. Six 2nd to 4th lactation cows were used for each treatment, in each period. Dry matter availability (DMA) was kept around to 1,800 and 1,500 kg/ha, for setaria-grass and ryegrass, respectively. Extras cows were used to keep DMA as proposed. Fat corrected, milk produced per animal and per area and the stocking rates observed were: 12.2, 10.8, and 8.7 kg/cow/day; 28.1, 24.4, and 21.7 kg/ha/day; and, 2.3, 2.3 and 2.5 cows/ha, respectively for treatments T1, T2 and T3.